2004
DOI: 10.1089/109065704323016067
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Alleles Associated with HIV Resistance in Russia

Abstract: Genetic polymorphisms of CCR5, CCR2, and SDF1 genes have been associated with resistance during human immunodeficiency virus type 1 (HIV-1) infection and disease progression. In the present report, we studied the frequency and co-occurrence of CCR5Delta32, CCR5-59029A/G, CCR2-64I, and SDF1-3'A allelic variants among HIV-1-seronegative individuals (n = 171) in Moscow. Observed allelic frequencies were 0.0906 [95% confidence interval (CI), 0.06-0.1212] for CCR5Delta32, 0.4072 (95% CI, 0.3542-0.4602) for CCR5-590… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
2
5
0
1
Order By: Relevance
“…Genotypic frequency of CCR2-64I observed in our study group (18.2%) is in accordance with that reported in South Indians (3-17%) (Ramana et al, 2001). This mutant allele is present in relatively higher frequencies (11-25%) in the Southeast Asian population (Apostolakis et al, 2005;Lewandowska et al, 2002;Martinson et al, 2000;Royo et al, 2001;Ryabov et al, 2004;Su et al, 1999) (Table 3). The CCR2-64I mutation even in its heterozygous state is reported to be associated with delayed progression to AIDS, thus contributing to the genetic resistance of the HIV-1 infected population developing AIDS (Kostrikis et al, 1998;Martin et al, 1998;Mulherin et al, 2003;Smith et al, 1997a,b).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Genotypic frequency of CCR2-64I observed in our study group (18.2%) is in accordance with that reported in South Indians (3-17%) (Ramana et al, 2001). This mutant allele is present in relatively higher frequencies (11-25%) in the Southeast Asian population (Apostolakis et al, 2005;Lewandowska et al, 2002;Martinson et al, 2000;Royo et al, 2001;Ryabov et al, 2004;Su et al, 1999) (Table 3). The CCR2-64I mutation even in its heterozygous state is reported to be associated with delayed progression to AIDS, thus contributing to the genetic resistance of the HIV-1 infected population developing AIDS (Kostrikis et al, 1998;Martin et al, 1998;Mulherin et al, 2003;Smith et al, 1997a,b).…”
Section: Discussionsupporting
confidence: 91%
“…The global, ethnic and regional distribution of these HIV/AIDS protective mutation frequencies varies significantly giving each population a different genetic resistance profile to the HIV infection and AIDS progression (Apostolakis et al, 2005;Lewandowska et al, 2002;Libert et al, 1998;Martinson et al, 2000;Royo et al, 2001;Ryabov et al, 2004;Su et al, 1999). Among Asian Indians, only a single study conducted on South Indians is reported till date for all the three mutations (Ramana et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The binding epitope of antibodies which neutralize a wide spectrum of HIV isolates has been identified as the third hypervariable loop (V3 loop) of gp120. This region is a surface accessible loop formed by a disulfide bridge between two conserved cysteines at positions 303 and 338 of gp120 and has been shown to bind to the chemokine co-receptors [36][37][38][39][40][41]. Its amino acid sequence varies highly among individual isolates and determines the cellular tropism, thus co-receptor specificity of the virus.…”
Section: Gp120 V3 Peptide-ccr5 Mediated Deregulation Of T Lymphocyte mentioning
confidence: 99%
“…One of such factors is the genetic resistance caused by 32 bp deletion in CCR5 gene can have the effect on limitation of infection. In Europe the prevalence of 32 bp deletion in the human β-chemokine receptor gene is ranked between 16% in the North Europe to 4% in the South Europe [15][16][17][18][19][20][21][22][23][24][25]. In Poland the frequency of deletion was assessed at 10.9% [26].…”
Section: Discussionmentioning
confidence: 99%